Zoledronate as effective treatment for minimal trauma fractures in a child with STAT3 deficiency and osteonecrosis of the hip. Issue 11 (14th July 2016) - Staines Boone, Aidé Tamara; Alcántara‐Montiel, Julio César; Sánchez‐Sánchez, Luz María; Arce‐Cano, Marina; García‐Campos, Jorge; Lugo Reyes, Saúl Oswaldo
Abstract: Signal transducer and activator of transcription 3 (STAT3) deficiency is a primary immunodeficiency characterized by eczema, complicated recurrent infections, elevated serum immunoglobulin E (IgE), osteopenia, and minimal trauma fractures. Zoledronic acid (ZA) is a long‐acting bisphosphonate that has been successfully used in children with secondary osteoporosis and osteogenesis imperfecta. We describe the case of a 7‐year‐old male with STAT3 deficiency and minimal trauma fractures, who also developed osteonecrosis of the hip. He responded well to intravenous ZA every 6 months for 18 months. Three years later, he walks independently and unaided, and has not suffered any other fractures. Although more studies are needed, ZA might help reduce minimal trauma fractures in patients with STAT3 deficiency.